Thematic and lexical paradigm of taboo in the Kazakh language (Eurasian Journal of Philology Science and Education, 2021)
The article describes the thematic-linguistic paradigm of taboo words, one of the main concepts in the field of lexicology and ethnolinguistics. Taboo is a term taken from the religious and ritual principles of Polynesia and currently adopted to establish a system of special prohibition in Ethnography and linguistics. The word «taboo» entered European languages for the first time based on captain Сook’s records of the third voyage to the world. In 1771, in the territory of Polynesia, namely the tango Islands, captain Сook established that the word«taboo» is used depending on certain forbidden customs. The article examines taboos from the point of view of Ethnography and linguistics. Also the article defines thematic features with an emphasis on the semantic structure of taboos in the Kazakh language. In accordance with this, a thematic and linguistic paradigm of taboo is created based on linguistic analysis. German psychologist V. Wund considers words to be the most ancient spiritual code of humanity, and A. Radcliffe-Brown noted that behavior aimed at taboo is a means of strengthening important rules and values to support society. Taboo also clarifies the boundaries between them, taking on two categories from the point of view of culture. Currently, taboo is considered as a universal phenomenon that takes place in society and fulfills these tasks. Paradigm – a theory obtained as an example for solving the problem under study; a system of combining theoretical views, methodological principles, methodological perception, and empiric results. And the thematic-linguistic paradigm of taboo is the classification and interpretation of semantic groups, considering various directions based on the analysis of data and research, the opinions of scientists related to this concept.